Crystal structure of 1-cyclopropyl-7-ethoxy-6,8-difluoro-4-oxo-1,4-dihydro-quinoline-3-carboxylic acid, C15H13F2NO4 - Zhang Chun-Yan; Nie Xu-Liang; Huang Guo-Ping; Xiong Yuan-Zhen; Huang Jian-Ping (Zeitschrift für Kristallographie - New Crystal Structures)
C15H13F2NO4, monoclinic, P21/n (no. 14), a = 5.1342(10) Å, b = 9.6478(18) Å, c = 27.192(5) Å, β = 95.42°, V = 1340.9(4) Å3, Z = 4, R gt(F) = 0.0434, wR ref(F 2) = 0.1197, T = 296(2) K.